Design and development of three-row improved pull-type rice transplanter for small farmers - SELVAN, M MUTHAMIL; ANNAMALAI, S J K; THAVAPRAKASH, N; ANANATHAKRISHNAN, D (The Indian Journal of Agricultural Sciences, 2014)
A pull-type transplanter was developed by improvising the functional components of existing six-row manual IRRI rice transplanter. The improved transplanter is capable of planting seedlings in three rows at 250 mm row spacing. Picker mechanism was designed in such a way to perform the planting operation simultaneously as the equipment is being pulled with handle. Thus the push-pull mechanism adopted in the existing transplanter has been eliminated in this improved model, reducing drudgery of operation. While evaluating the unit in different puddling conditions as well as textural conditions, the field capacity was observed as 0.058 ha/h with field efficiency of 85.4% at the draft of 261.7 N. Percentage of missing hills was found as 9.61 with the optimized growing density of seedling of 60 g/mat. The ground wheel diameter was optimized as 500 mm based on intra-row spacing as well as force requirement for pulling the unit. The picker-finger width of 3 mm was optimized as there was high mortality rate observed with other fingers. For the optimized picker-finger width, single seedling was observed in 12.1% hills, double seedlings in 30.4% hills, triple seedlings in 31.7% hills, and 25.8% hills are planted with more than three seedlings. By employing ergonomic consideration in seedling picking mechanism, the energy requirement with improved transplanter was reduced to 19.84 kJ/min from 26.41 as in existing transplanter, and hence there was 24.9% reduction in drudgery. Although energy cost with improved transplanter is graded as ‘heavy’, the unit can be operated effectively with the recommended rest-pause of 12.5 min for every 45 min. Cost of transplanting with the equipment worked out ` 1 150 per ha with a cost-saving of 80.8% in addition to time-saving of 91.3% compared to hand transplanting. The improved transplanter has good scope for introduction in marginal farms.